Rechargeable lithium battery with composite anode

By using metal nitrogen compounds embedded in transition metal-containing mesh structures as composite anode materials in lithium batteries, the problems of low energy density and rare metals in existing lithium-ion batteries are solved, and high energy density and safety are achieved.

CN112913046BActive Publication Date: 2025-03-18HUBER ENGINEERED MATERIALS DEUTSCHLAND GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN201980057971.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-09-05
Filing Date
2019-09-05
Publication Date
2025-03-18
Estimated Expiration
2039-09-05

AI Technical Summary

Technical Problem

The existing lithium-ion batteries have low energy density and the cathode materials used contain rare and difficult to obtain metals, which affects their sustainability and safety.

Method used

A composite anode is used, containing a metal nitrogen compound as an electrochemically active component, and is separated from the cathode by a separator, which contains a compound capable of inserting lithium and an aprotic lithium electrolyte. The metal nitrogen compound in the anode is embedded in an electron-conductive or mixed-conductive network structure containing transition metals.

Benefits of technology

High energy density (500Wh/kg or higher) and good safety characteristics are achieved, avoiding the use of lithium metal and its alloys, and reducing dependence on rare metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004912448180000011
    Figure GDA0004912448180000011
  • Figure GDA0004912448180000051
    Figure GDA0004912448180000051
  • Figure GDA0004912448180000064
    Figure GDA0004912448180000064
Patent Text Reader

Abstract

The present invention relates to a rechargeable lithium battery, the rechargeable lithium battery comprising: a composite anode (negative electrode), wherein the composite anode contains a metal nitrogen compound of the following general formula (I) and / or general formula (II) as an electrochemically active component: Li x M 2 z (NH) 0.5x+z (I)Li m M 2 n (NH 2 ) 1+n (II), wherein (I) and (II) are present in any mixing ratio, and M 2 = an alkaline earth element selected from the group consisting of Mg, Ca, Sr, Ba or any mixture thereof, wherein x=0-4; z=0-2; m=1 or 0; n=1 or 0, wherein (m+n)=1, and wherein these correspond to the most lithium-poor charge state of the fully discharged nitrogen-containing compound; and a cathode (positive electrode) separated from the composite anode by a separator, the cathode comprising a compound capable of inserting lithium selected from metal oxides, lithium metal oxides, lithium oxides and lithium hydroxide, and comprising an aprotic lithium electrolyte, wherein the electrochemically active metal nitrogen compound of the composite anode is embedded in an electronically conductive or mixed conductive network structure containing a transition metal, the network structure being composed of finely distributed transition metals and / or electronically conductive or mixed conductive interstitial transition metal compounds, and the weight ratio between the components forming the network structure and the nitrogen-containing compounds I and / or II is in the range of 1:100 to 1:2.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to a rechargeable lithium battery, which comprises: a composite anode, in which a metal nitrogen compound is contained as an electrochemically active component; a cathode separated from the composite anode by a separator, and the cathode comprises a compound capable of inserting lithium and a non-protonic lithium electrolyte. Prior art

[0002] The operating principle of commercial rechargeable lithium-ion batteries is based on the insertion mechanism: both the negative electrode (anode) and the positive electrode (cathode) are made of materials that are able to store (insert) lithium ions without fundamentally changing the microstructure. Although carbon-based materials (graphite or hard carbon) are used as anode materials, the cathode active materials consist of transition metal oxides. The transition metals in the latter oxides are redox active, i.e. they change their oxidation state during charging or discharging. This is illustrated by the following exemplary reaction:

[0003]

[0004] For currently used cathode materials, when charging / discharging the battery, the oxidation state of the redox-active metal center changes only by one order, in the above case, between +III and +IV. For this reason, the capacity of the cathode material is relatively low. In the conventional cathode material LiCoO 2 In the case of LiC, the theoretical capacity is 274 mAh / g, of which only about 135 mAh / g is actually available. 6 , the graphite material used for the anode also has a relatively low capacity of 372 mAh / g. 6 ) / LiCoO 2 The theoretical energy density of the system is also unsatisfactorily low, at about 380 Wh / g. Another disadvantage of lithium-ion batteries is that the cathode materials used are mainly elements of low availability, such as cobalt and nickel. It is worrying that the metals are not available in sufficient quantities to provide a comprehensive supply of lithium batteries for electric vehicles and stationary energy storage worldwide.

[0005] Lithium metal, which replaces graphite, has a significantly higher storage capacity (3860 mAh / g), which cannot be used to produce anodes in practical batteries because such batteries are neither safe nor cycle stable. During cycling, lithium metal is sometimes not deposited in a planar manner, but in the form of needle-like growths (dendrites). These growths can lose physical contact with the metal anode, resulting in a corresponding reduction in the capacity of the electrochemical cell. If such sharp dendrites penetrate the separator, the consequences are even more serious. As a result, the battery cell can short-circuit, often with catastrophic consequences: thermal runaway, opening of the battery housing and possible ignition of escaping gases.

[0006] Therefore, efforts are being made to use lithium alloys instead of pure lithium metal as anode materials. However, lithium alloys show extremely strong volume fluctuations (sometimes several hundred %) during storage and recovery of lithium, such as Li 9 Al 4 : 238%). For this reason, alloy anodes other than tin-graphite composites have not been able to establish themselves on the market so far. Tin is toxic and is a rare and expensive element, which prevents the widespread use of tin-containing materials.

[0007] As an alternative to cationic redox-active cathode materials, open cell systems have been investigated. They consist of a structure open to the surroundings, which is porous and consists mainly of carbon, the surface of which is coated with a catalyst containing a noble metal, so that diffused oxygen can combine to form lithium oxide (oxygen reduction reaction):

[0008] Li + +e - +O 2 →LiO 2

[0009] The initially formed product, lithium superoxide (LiO 2 ), the average oxidation number of oxygen is -0.5. Further absorption of lithium will produce lithium peroxide (Li 2 O 2 ). The latter lithium oxide can be converted into lithium and elemental oxygen in the presence of a metal catalyst that catalyzes the oxidation of oxygen in the reverse reaction of the formation reaction:

[0010] Li 2 O 2 →2Li + +2e - +O 2

[0011] Unfortunately, the above-mentioned air electrodes have only very low power density and, most importantly, only very limited reversibility, so this cathode shape is still far from being used in commercial batteries. In addition, there is a large difference of typically 0.5-1V between the charging potential and the discharging potential, so the energy efficiency ("round trip efficiency") is completely unsatisfactory. Due to the technical challenges that cannot be overcome at present, it is expected that the commercialization of lithium / air batteries will be carried out in 10-20 years at the earliest. For a review, see K. Amine et al., Chem. Reviews 2014, 5611-40, 114.

[0012] Issues to be resolved

[0013] The object of the present invention is to provide a lithium battery having a high energy density of 500 Wh / kg or more and good safety characteristics, wherein the lithium metal anode is omitted and an active material having a content of rare or difficult-to-obtain metals as low as possible is used.

[0014] Solution to the problem

[0015] The object is achieved by a rechargeable lithium battery comprising a composite anode (negative electrode) comprising a metal nitrogen compound of the general formula (I) and / or the general formula (II) as an electrochemically active component

[0016] Li x M 2 z (NH) 0.5x+z (I)

[0017] Li m M 2 n (NH 2 ) 1+n (II), where

[0018] (I) and (II) are present in any mixing ratio, and

[0019] M 2 = an alkaline earth element selected from the group consisting of Mg, Ca, Sr, Ba or any mixture thereof, wherein

[0020] x=0-4; z=0-2;

[0021] m=1 or 0; n=1 or 0, where (m+n)=1, and where these correspond to the fully discharged most lithium-poor charge state of the nitrogen-containing compound;

[0022] A cathode (positive electrode) separated from the composite anode by a separator, the cathode comprising a compound capable of inserting lithium selected from metal oxides, lithium metal oxides, lithium oxides and lithium hydroxide, and comprising an aprotic lithium electrolyte, wherein the electrochemically active metal nitrogen compound of the composite anode is embedded in an electronically conductive or mixed conductive network structure containing a transition metal, the network structure is composed of finely distributed transition metals and / or electronically conductive or mixed conductive interstitial transition metal compounds, and the weight ratio between the components forming the network structure and the nitrogen-containing compounds I and / or II is in the range of 1:100 to 1:2.

[0023] In the context of the present invention, electronically conductive or mixedly conductive networks are understood to mean purely electronically conductive materials or materials that are simultaneously ionically and electronically conductive. In the fully charged, most lithium-rich state of the metal nitride compounds, they correspond to the general formula (III) and / or (IV)

[0024] Li 2z+x M 2 z (NH) 0.5x+z (III)

[0025] Li 3 N . n(LiM 2 N) . (4-2m)LiH(IV), where

[0026] (III) and (IV) are present in any mixing ratio, and

[0027] M 2 =Alkaline earth elements (Mg, Ca, Sr, Ba or any mixture thereof)

[0028] x=0-4; z=0-2

[0029] m=1 or 0; n=1 or 0, wherein (m+n)=1.

[0030] For the cathode, the relative Li / Li + The cathode material has an electrochemical potential exceeding a value of about 2 V. Preferably, a cathode material selected from lithium hydroxide (LiOH), lithium oxide (Li 2 O), lithium peroxide (Li 2 O 2 ) and lithium superoxide (LiO 2 ) nanoparticle lithium oxygen compound embedded in an electronically conductive or mixed conductive network. In the case of using LiOH, at least after the first charge, the cathode additionally contains lithium hydride (LiH).

[0031] The rechargeable lithium battery according to the invention has a high reversible storage capacity without having to use lithium metal or a material capable of forming an alloy with lithium (eg tin, silicon or aluminum) as an anode. The functional principle of the electrochemically active anode material is explained below.

[0032] When a galvanic cell comprising a nitrogen-containing active material according to the present invention is charged / discharged, the general anode half reaction corresponds to at least one of the following two reaction equations:

[0033]

[0034] In order to obtain a particularly high specific capacity, it is preferred that M2 has the lowest possible atomic mass, i.e., M 2 Preferred is magnesium (Mg) or calcium (Ca) or a mixture thereof.

[0035] Preferably, the galvanic cell in the discharged (lithium-deficient) state comprises one or more of the following compounds according to formula (I): Li 2 NH, MgNH, CaNH, Li 2 Mg(NH) 2 , Li 2 Ca(NH) 2 MgCa(NH) 2 , Li 4 Mg(NH) 3 , Li 2 Mg 2 (NH) 3 , and / or one or more of the following compounds according to formula (II): LiNH 2 , Ca(NH 2 ) 2 or Mg(NH 2 ) 2 , as the active anode material.

[0036] If the galvanic cell according to the invention is charged by applying an external voltage, the N-containing active anode material enters a lithium-rich state. When fully charged, the following lithium-rich compounds are formed, preferably according to the general formula (III): Li 4 NH, Li 2 CaNH, Li 2 MgNH、Li 6 Mg(NH) 2 , Li 6 Ca(NH) 2 , Li 4 MgCa(NH) 2 , Li 10 Mg(NH) 3 , Li 8 Mg 2 (NH) 3 , and / or according to the general formula (IV), preferably: Li 3 N, CaLiN, MgLiN and LiH.

[0037] Imido compounds containing more than one metal can be phase-pure compounds, such as Li 4 M 2 (NH) 3 or Li 2 M 2 2 (NH) 3 (M2 =Mg, Ca, Sr or Ba) type compounds or physical mixtures of the corresponding monometallic compounds. For example, it is known from the literature that Li 4 Mg(NH) 3 , which is formally Li 2 Mg(NH) 2 and Li 2 A mixture of NH (see KJ Michel, ARA Akbarzadeh, V. Ozolins, J. Phys. Chem. C. 2009, 113, 14551-8), and Li 2 Mg 2 (NH) 3 , namely Li 2 Mg(NH) 2 and MgNH mixed compounds (see E. Weidner et al., J. Phys. Chem. C 2009, 113, 15772-7).

[0038] The electrochemical redox half reactions of the four exemplary compounds of formula (I) can be described as follows:

[0039]

[0040] and

[0041]

[0042] as well as

[0043]

[0044] and

[0045]

[0046] The theoretical capacities of the seven particularly preferred anode systems listed above are calculated based on the discharged (lithium-poor) form and are as follows:

[0047] Table 1: Theoretical electrochemical capacities of selected nitrogen-containing anode active materials

[0048]

[0049] Thus, all particularly preferably used anode materials according to the general formula (I) or (II) have at least three times the theoretical capacity compared to the prior art (graphite).

[0050] In addition to the compounds of the general formula (I) to (IV) described above, compounds of the general formula M 2 2 LiNH 2 (where M2 =Mg, Ca, Sr, Ba or any desired mixture thereof). A typical example is Sr 2 LiNH 2 (See DM Liu, QQ Liu, TZ Si, QAZhang, Journal of Alloys and Compounds, 495, April 9, 2010, 272-274), which can be used as a lithium nitrogen-based anode material with high capacity for the purpose of the present invention.

[0051] Among the lithium-deficient anode active materials according to the present invention, lithium amide has the highest lithium absorption capacity (see Table 1). By using a mixture of lithium amide and an anode material according to general formula (I), the electrochemical specific capacity can be increased. For example, when lithium amide and lithium imide Li 2 When the mixture is 1:1 with NH, the theoretical specific capacity of the obtained mixed anode material is 3103Ah / kg. The electrochemical half reaction of the mixture is described by the following reaction formula:

[0052]

[0053] LiNH 2 The addition of Li can be achieved by mixing the pure components; it is also possible, for example, to 3 Hydrogenation of N to the desired H content to synthesize a structurally homogeneous mixed phase Li 2-x NH 1+x (See D. Chandra et al., DOE Hydrogen Program, FY2009 Ann. Prog. Rep. 477-482).

[0054] The lithium nitrogen-based anode active material can be prepared by the synthesis routes listed in WO 2011 / 051290 A1 and WO 2011 / 121084 A1, respectively.

[0055] From patents WO 2011 / 051290 A1 and WO 2011 / 121084 A1, lithium nitrogen compounds according to the general formula (I), (II), (III) and (IV) are known as high-capacity anode materials. Both documents clearly state that the battery anodes produced therefrom should not contain transition metals. In addition, in WO 2011 / 051290 A1, "Li o NH 3-o A transition metal-free lithium nitrogen compound, wherein o=1, 2 or 3".

[0056] WO 2011 / 121084 A1 does not explicitly state that no transition metal is present in the anode, but there is no indication that a transition metal or a transition metal compound may be present in the negative ground (anode).

[0057] The present inventors have found that lithium nitrogen compounds according to the general formulae (I) to (IV) when used as anode materials according to the technical teachings of WO 2011 / 121084 A1 and WO 2011 / 051290 A1 have very low electrochemical capacity and almost no reversibility when cycling of galvanic cells produced therefrom is attempted.

[0058] It has now been surprisingly found that by adding relative to Li / Li + Finely distributed transition metal powders and / or finely distributed conductive transition metal compounds with an electrochemical potential of <2.5 V can significantly improve the electrochemical activity and cycling capacity. It is important to ensure that the lithium nitrogen-based anode material is in contact with the finely distributed transition metal powder or conductive transition metal compound as closely as possible. In addition, it is advantageous that the lithium nitrogen compound and transition metal powder characterized by the general formula (I)-(IV) and the Li / Li + The electronically conductive or mixed conductive transition metal compound with an electrochemical potential of <2.5 V is present in the form of amorphous or nanoparticles that are as finely distributed as possible. The exact size of the preferred nanoparticle form depends on the mechanical form factor (i.e. the three-dimensional shape of the particles). In the case of spherical (or similar) particle forms, these sizes are 0.1-100 nm, preferably 1-30 nm. Relative to Li / Li + The electrochemical potential of the finely distributed transition metal powder and / or the finely distributed conductive transition metal compound is <2.5 V and the conductivity at room temperature is at least 10 -7 S / cm, preferably at least 10 -6 S / cm and particularly preferably at least 10 -5 S / cm.

[0059] Preferably, elements from Groups 3 to 12 of the Periodic Table of the Elements, particularly preferably M=Sc, Ti, Zr, Hf, V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Ag, Zn, and rare earth metals La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Tm, Yb and Lu or any mixture of the transition metals are used as transition metal powder M.

[0060] The electron-conducting interstitial compound is used as the relative Li / Li +The interstitial compounds are preferably transition metal nitrides (metal nitrides) and / or transition metal carbides, where M = a metal from Group 3 to Group 12 of the Periodic Table, and / or transition metal hydrides, where M = a metal from Group 3 to Group 10 of the Periodic Table. Binary (MN) x , MC x MH x ) and ternary (MM' y N x ;MM' y C x ;MM' y H x ) and higher mixed phases, wherein the additional metal M' is at least one other transition metal (M) selected from Groups 3 to 12 of the Periodic Table of Elements x M' y N z ) and / or elemental lithium (Li y MN x ;Li y MC x ;Li w M x M' y N z ;Li w M x M' y H z ; etc.). Here: w, y = 0 to 8; x = 0.5 to 1; z = 0 to 3.

[0061] Nanoparticles of metal nitrides can be prepared, for example, by grinding crystalline precursors using a high-energy grinder (planetary ball mill) (DH Gregory, The Chemical Record, Vol. 8, 229-239, 2008). However, they can also be prepared by other physical processes such as physical vapor deposition, plasma and laser methods or by chemical processes. The chemical process is usually based on elemental metals or corresponding compounds (oxides, hydrides, etc.), and can react with nitrogen sources such as ammonia, cyanamide, urea or gaseous nitrogen at high temperatures (S. Dong et al., Coordination Chem. Reviews 257 (2013) 1946-56). Highly conductive nanoporous transition metal nitrides can be prepared, for example, by ammonolysis of oxide precursors containing Zn and Cd (M. Yang, J. DiSalvo, Chem. Materials 2012, 24, 4406-9). The following transition metal nitride compounds are particularly preferably used: TiN n 、ZrN n , HfN n 、VNn 、NbN n 、TaN n CrN n 、MoN n , WN n 、MnN n ,FeN n , CoN n 、NiN n 、ZnN n Cr 1-n Fe n N, wherein n = 0.3 to 1, and Li 7 Mn 4 ;LiMoN 2 ;Li 2.6 Co 0.2 Cu 0.15 Fe 0.05 N; Li 2.7 Fe 0.3 N; Li 3 FeN 2 ;Li 2.5 Co 0.2 Cu 0.1 Ni 0.1 N; Li 2.6 Co 0.2 Cu 0.2 N; Li 2.6 Co 0.4 N.

[0062] Transition metal carbides can be prepared by carbothermal reduction, co-reduction process, hydrothermal method, sol-gel process and CVD process. Nanoparticle carbides with 1D or 2D morphology are usually synthesized by template method (Y. Zong, Adv. Sci. 2016, 3, 1500286). The following transition metal carbide compounds are particularly preferably used: TiC, WC; ZrC 1-m , HfC 1-m VC 1-m , NbC 1-m 、TaC 1-m Cr 3 C 2 、MO 2 C.Fe 3 C, wherein m = 0 to 0.5.

[0063] Transition metal hydrides are generally prepared by hydrogenating the base metal, usually at elevated temperature and hydrogen pressure (U. Wietelmann, M. Felderhoff, P. Rittmeyer, Ullmann's Encyclopedia of Industrial Chemistry, "Hydrides", A13, 2016, Wiley-VCH, Weinheim). The following transition metal hydride compounds are particularly preferably used: ScH 2 , YH o , LaH o , CeH 2 , PrH o , NdH o , SmH o ,EuH o , GdH o , TbH o ,DyH o 、HoH o , ErH o , TmH o , YbH o , LuH o 、TiH 2 , ZrH 2 , HfH 2 , VH, VH 2 , TaH 0.5 , MnH, where o=2 or 3.

[0064] The above listed has a qualitative composition Li w M x M' y E z (E = N, C, H; w, y = 0 to 8; x = 0.5 to 1; z = 0 to 3) belong to the group of so-called interstitial metal compounds or alloys, i.e. the incorporated foreign elements E, i.e. carbon, nitrogen and hydrogen, are arranged in the interstitial layers (interstitial spaces) of the underlying metal lattice. The specified stoichiometry indicates the maximum content of carbon, nitrogen or hydrogen (limiting stoichiometry). However, interstitial compounds are not completely stoichiometric compounds, i.e., generally, all combinations starting from the pure metals up to the specified limiting stoichiometry are possible and mostly stable. The qualitative expression is L w M x M' y E z-δ All compounds with a low foreign element content (δ can have any value between 0 and z) are also electronically conductive or mixed conductive materials and are therefore suitable for preparing composite anodes according to the invention with nitrogen-containing active materials.

[0065] According to the invention, the nanoparticulate, electronically conductive transition metal and / or its likewise nanoparticulate nitride, carbide or hydride can be mixed as uniformly as possible with the likewise nanoparticulate, lithium-nitrogen-containing anode material by means of a physical mixing process, wherein good contact of the individual particles is ensured during the anode stripping production by subsequent pressing (calendering in the case of industrial-commercial production) and a fully functional nitrogen- and transition-metal-containing composite anode is obtained. The composite anode material according to the invention can also be prepared by chemical processes, for example by reaction with a nitrogen source. A preferred nitrogen source is elemental nitrogen (N 2 ); ammonia (NH 3 ); Hydrazine (N 2 H 4 ); urea (CH 4 N 2 O). When using NH 3 In the ammonolysis, the metals, namely lithium and the corresponding transition metals, are reacted with ammonia, preferably at elevated temperature and pressure. The amino compounds obtained can then be further converted by subsequent pyrolysis, for example to form imino compounds and / or nitrides. If non-nitride conductivity enhancers are required, suitable transition metal hydrides and / or transition metal carbides can be added before or after the ammonolysis (option: see above). After removal of excess ammonia, the remaining solid can be ground. This measure reduces the particle size and improves contact. When reacting with nitrogen, mainly at elevated temperature and pressure, nitride phases are immediately formed. In this case as well, the desired non-nitride conductivity enhancers can be added.

[0066] In a preferred configuration of the invention, the lithium nitrogen-containing anode material of the invention is co-milled with a conductivity-enhancing transition metal or its nitride, carbide or hydride. The milling is carried out using a high-energy mill, for example a planetary ball mill type.

[0067] Other materials that improve the functionality of the anode can be added to the nitrogen-containing composite anode material according to the invention. These materials mainly include non-metal-based conductivity enhancers, lithium-providing additives and binders. Potential non-metal-based conductivity enhancers include, in particular, conductive forms of elemental carbon (graphite, carbon black, graphene, carbon nanotubes). Lithium metal (preferably coated, i.e. surface passivated and in powder form or film form) or lithium-rich compounds such as lithium graphite (LiC 6-δ , δ = 0-5) or coated lithium silicide (Li n SiO x @Li 2 O, n = 0.5-4.4; x = 0-1) can be used as additives to provide lithium. Organic polymers commonly used in electrode manufacturing can be used as binders. These polymers include PTFE, PVdF, polyisobutylene (e.g., from BASF ) and similar materials.

[0068] In the composite anode material containing nitrogen and transition metals according to the invention, on the one hand, finely distributed transition metals or electronically conductive or mixed-conductive transition metal compounds Li w M x M' y E z The weight ratio between (E=N, C, H; w, y=0 to 8; x=0.5 to 1; z=0 to 3) and the nitrogen-containing electrochemically active nitrogen-containing anode material on the other hand is in the range of 1:100 to 1:2. It is preferably in the range of 1:50 to 1:5.

[0069] The final nitrogen and transition metal-containing composite anode according to the present invention may additionally comprise other conductivity enhancers (0 to 30 wt %), binders (0 to 20 wt %), and / or pre-lithiation agents (0 to 20 wt %).

[0070] In principle, the composite anode materials containing nitrogen and transition metals according to the invention can be used to produce rechargeable lithium batteries with any counter electrode. However, the electrochemical potential of the cathode active material used is relatively low relative to Li / Li + The reference electrode should be at least 2.0 V, preferably at least 2.5 V. Useful cathode materials include in particular lithiated metal oxide insertion materials, preferably layered compounds such as LiCoO 2 、LiNiO 2 、Li(Ni,Mn,Co)O 2 、LiNi 0.80 Co 0.15 Al 0.05 O 2 And spinel structure materials such as LiMn 2 O 4 and LiNi 0.5 Mn 1.5 O 4 As well as materials with olivine structure such as LiFePO 4 and LiMnPO 4 Non-lithiated metal insertion compounds such as electrolytic manganese dioxide (MnO 2 ) or vanadium oxide (V 2 O 3 ). The molecular formulae listed above each represent an ideal composition of a basic compound. In practice, however, they are used in slightly or more severely modified forms. They include materials with structural stabilization doping (e.g., aluminum-stabilized lithium nickel cobalt oxide, "NCA") or compounds doped with foreign metals or nonmetals to increase conductivity. Such variants of the parent compound modified by doping can also be used according to the invention. According to the invention, mixtures of different cathode materials can also be used.

[0071] Preferably, a positive electrode (cathode) is used, the electrochemically active component of which is an anionic redox-active material in the form of at least one lithium oxygen compound selected from the group consisting of lithium hydroxide (LiOH), lithium oxide (Li 2 O), lithium peroxide (Li 2 O 2 ) and lithium superoxide (LiO 2 ).

[0072] When charging / discharging a galvanic cell according to the invention using the preferred anionic redox active materials, the general cathode half reaction corresponds to at least one of the following reactions:

[0073]

[0074] Compared with LiCoO 2 Preferably, the cathode material used has a capacity which is at least 4 times higher than the theoretical capacity of 200 Å.

[0075] Table 2: Theoretical electrochemical capacities of preferred anionic redox-active cathode materials

[0076]

[0077] Since all the lithium oxygen compounds described are electronic insulators, they must be present in finely distributed (amorphous or nanoparticle) form and the individual particles must be in contact using an electronically conductive or mixed conductive network. For this example, finely distributed conductive metals and many metal oxides and lithium metal oxides can potentially be used. Such systems are known from the literature and only exemplary embodiments are given here. Lithium peroxide Li 2 O 2 By mixing with conductive LiNi 0.33 Co 0.33 Mn 0.33 O 2 The co-metal and Li are in the form of nanoparticles. 2 Composite materials composed of mixtures of O can also be completely decomposed cathodically (Y. Sun, Nature Energy, January 2016, 15008). For the purpose of the present invention, the charging voltage should not exceed a specific level at which oxygen begins to escape. For lithium oxides, this voltage is relative to Li / Li + is about 3-3.5V. Contains Co embedded 3 O 4 Nanoparticles of lithium oxide (Li 2 O. Li 2 O2 and LiO 2 The actual functionality of a complete battery cell (of a mixture of) is known (Z. Zhi, Nature Energy, July 25, 2016, 16111).

[0078] The types familiar to the person skilled in the art (liquid, gel, polymer and solid electrolytes) can be used as electrolytes for the anionic redox cells according to the invention with composite anodes containing nitrogen and transition metals. Soluble lithium salts with weakly coordinated oxidation-stable anions in the matrix used are used as conducting salts for liquid polymer and gel polymer systems. These lithium salts include, for example, LiPF 6 , Lithium fluoroalkyl phosphate, LiBF 4 , imino salts (e.g. LiN(SO 2 CF 3 ) 2 ), LiOSO 2 CF 3 , methylated salts (e.g. LiC(SO 2 CF 3 ) 3 ), LiClO 4 , chelated lithium borate (e.g. LiB(C 2 O 4 ) 2 , called "LiBOB"), fluoro-chelated lithium borate (such as LiC 2 O 4 BF 2 , called "LiDFOB"), chelated lithium phosphate (e.g. LiP(C 2 O 4 ) 3 , called “LiTOP”) and fluorinated lithium chelate phosphates (e.g. Li(C 2 O 4 ) 2 PF 2 ). Salts of anions which are stable to anionic dissociation and free of fluorine are particularly preferred.

[0079] Solid electrolytes, i.e., lithium ion conductive glasses, ceramics or crystalline inorganic solids are also particularly preferred. Examples of such materials include lithium thiophosphates (e.g., Li 3 PS 4 ), Argentum (Li 6 PS 5 X, where X = Cl, Br, I), phosphosilicates (e.g. Li 2 SiP 2 ), nitrogen phosphates (such as Li 2.9 PO 3.3 N 0.36), nitrogen borophosphate (such as Li 47 B 3 P 14 N 42 ), metal thiophosphates (such as Li 10 G 2 S 11 ), garnet (such as Li 7 La 3 Zr 2 O 12 ), titanium phosphate (Li 1.5 Al 0.5 Ti 1.5 (PO 4 ) 3 ) and borohydride compounds (such as LiBH 4 , Li 2 B 12 H 12 ).

[0080] The nitrogen- and transition metal-containing composite anode materials according to the invention can be used to construct the galvanic cell according to the invention. Depending on the type of counter electrode (cathode), they can be used for this purpose in (partially) lithium-charged or (partially) discharged (delithiated) form. When using the delithiated anode form, the opposite applies to the lithiated anode form when using the lithium-charged cathode material. This is illustrated below using some examples:

[0081] The lithium-free anode forms such as lithium imide (Li 2 NH), relative to the lithium-rich cathode material, the lithium-rich cathode material is preferably selected from the following 2 O and Li 2 O 2 At least one of the compounds can be constructed to form an electrochemical cell. The electrochemical redox reaction is as follows:

[0082]

[0083] In contrast, lithium-rich forms of preferred anode materials, such as Li 2 MgNH or Li 4 NH, suitable as a cathode material in the lithium-deficient form according to the present invention (e.g. LiOH, LiO 2 ) counter electrode. Lithium peroxide can also be used, which can absorb more lithium in combination with lithium-rich anode materials. Lithium peroxide with a moderate lithium content can therefore be used in combination with lithium-rich and lithium-poor anode active materials. The electrochemical reaction can be expressed as follows:

[0084]

[0085] When lithium amide is used, the charge / discharge reaction is, for example, as follows:

[0086]

[0087] When a partially lithiated form of the anode material is used, an amount of cathode material sufficient to absorb lithium may be used either in partially lithiated form or as a mixture of separate particles in lithium-charged and lithium-discharged form. Such methods of balancing the electrodes are familiar to those skilled in the art. The lithium required for complete lithiation may also be provided in the form of a separately added lithium-rich material such as lithium metal powder or lithium-rich metal alloy powder (e.g., Li-Si or Li-Sn alloy) (F. Holtstiege, M. Winter, T. Placke, Batteries 2018, 4, 4-39).

[0088] The present invention is illustrated by the following examples:

[0089] Comparative Example:

[0090] The lithium-nitrogen-containing microcrystalline powder anode material LiNH 2 or Li 2 NH was mixed with a transition metal-free conductivity enhancer (carbon black AB 100) and PTFE powder (supplier: Aldrich) in an Ar-filled glove box and briefly homogenized using an agate mortar. The weight ratio was 60 wt% active material; 25 wt% carbon black; 15 wt% PTFE. The electrode material was then applied to an area of ​​1 cm 2 The nickel powder is placed on a current collector and isostatically compressed at a pressure of 10 tons for one minute.

[0091] The anodes produced in this way were tested in a glass cell with a three-electrode arrangement. In addition to the lithium-nitrogen containing electrode, two electrodes made of lithium sheets were used as counter and reference electrodes. 11% LiPF in EC / DMC (1:1) 6 The solution serves as an electrolyte.

[0092] Using LiNH 2 The static potential of the battery is 1300mV. 2 The rest potential of the cell for NH is 700 mV. In both cases, the polarization is carried out at extremely low feed voltages, up to 5 mV. The amount of charge used for this purpose corresponds to almost 0.1 equivalent of lithium in each case. Subsequently, the polarity is reversed and the lithium is removed. In LiNH 2 In the case of Li 2 In the case of NH, about 0.55Li can be extracted.

[0093] Example 1: Preparation of a composite anode material containing nitrogen and transition metals by milling (hydride-based conductivity enhancer)

[0094] In a glove box filled with Ar, 4.2 g of lithium imide (Li 2 NH), 2.1 g zirconium hydride (S grade from Albemarle Germany, H content at least 1.9%) and 0.7 g carbon black (AB 100) were premixed in a beaker. The homogenized mixture was filled into a 50 mL zirconium ceramic grinding jar together with about 27 g of 3 mm zirconium ceramic balls and sealed. The mixture was then ground in a planetary ball mill (Pulverisette P7 from Fritsch) at 800 rpm for 90 minutes.

[0095] The grinding jar was returned to the Ar-filled glove box and opened there. The grinding product was separated from the grinding media by means of sieving.

[0096] Yield: 6.3 g gray-black fine powder

[0097] Example 2: Preparation of composite anode materials containing nitrogen and transition metals by milling (nitride-based conductivity enhancers)

[0098] In a glove box filled with Ar, 4.0 g of lithium imide (Li 2 NH) (x-ray purity 100%), 0.75 g titanium nitride (<3 μm, from Sigma-Aldrich) and 0.25 g carbon black (AB 100) were mixed in a beaker. The pre-homogenized mixture was filled into a 50 mL zirconium ceramic grinding jar together with about 27 g of 3 mm zirconium ceramic balls and sealed. The mixture was then ground in a planetary ball mill (Pulverisette P7 from Fritsch) at 800 rpm in reverse operating mode for 240 minutes.

[0099] The grinding jar was returned to the Ar-filled glove box and opened there. The grinding product was separated from the grinding media by means of sieving.

[0100] Yield: 4.1 g gray-black fine powder

[0101] Further aspects of the invention are provided by the subject matter of the following clauses:

[0102] Item 1. A rechargeable lithium battery, comprising: a composite anode, wherein the composite anode comprises a metal nitrogen compound of the following general formula (I) and / or general formula (II) as an electrochemically active component:

[0103] Li x M 2 z(NH) 0.5x+z (I)

[0104] Li m M 2 n (NH 2 ) 1+n (II), where

[0105] (I) and (II) are present in any mixing ratio, and

[0106] M 2 = an alkaline earth element selected from the group consisting of Mg, Ca, Sr, Ba or any mixture thereof, wherein

[0107] x=0-4; z=0-2;

[0108] m=1 or 0; n=1 or 0, where (m+n)=1,

[0109] wherein these correspond to the fully discharged, most lithium-poor charge states of the nitrogen-containing compound;

[0110] A cathode separated from the composite anode by a separator, the cathode comprising a compound capable of inserting lithium selected from metal oxides, lithium metal oxides, lithium oxides and lithium hydroxide, and comprising a non-protonic lithium electrolyte, characterized in that the electrochemically active metal nitrogen compound of the composite anode is embedded in an electronically conductive or mixed conductive network structure containing a transition metal, the network structure is composed of finely distributed transition metals and / or electronically conductive or mixed conductive interstitial transition metal compounds, and the weight ratio between the components forming the network structure and the nitrogen-containing compounds I and / or II is in the range of 1:100 to 1:2.

[0111] Item 2. The lithium battery according to Item 1, characterized in that the transition metal-containing electronically conductive or mixed conductive network structure comprises relative to Li / Li + Finely distributed nanoparticle transition metal powders M or interstitial transition metal compounds with an electrochemical potential < 2.5 V.

[0112] Item 3. The lithium battery according to Item 1 or 2, characterized in that the composite anode contains an element from Group 3 to Group 12 of the Periodic Table of Elements as transition metal powder M.

[0113] Item 4. A lithium battery according to Item 1 or 2, characterized in that the composite anode comprises an electronically conductive or mixed conductive interstitial compound selected from a transition metal nitride and / or a transition metal carbide of at least one element from Group 3 to Group 12 of the Periodic Table of the Elements, and / or a transition metal hydride of at least one element from Group 3 to Group 10 of the Periodic Table of the Elements.

[0114] Item 5. A lithium battery according to items 1 to 4, characterized in that the transition metal powder and / or mixed conductive interstitial transition metal compound and the electrochemically active metal nitrogen compound are present in a uniform mixture in the form of finely distributed amorphous or nanoparticles, wherein the particle size is in the range of 0.1-100 nm, preferably 1-30 nm.

[0115] Item 6. A lithium battery according to items 1 to 5, characterized in that the weight ratio between the finely distributed transition metal and / or the electronically conductive or mixed conductive interstitial transition metal compound and the nitrogen-containing active material in the composite anode is in the range of 1:50 to 1:5.

[0116] Item 7. A lithium battery according to Item 3, characterized in that the composite anode contains the following substances as a network structure containing an electronically conductive or mixed conductive transition metal: finely distributed transition metal powder M, where M = Sc, Ti, Zr, Hf, V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Ag, Zn and rare earth metals La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Tm, Yb and Lu or any mixture of the transition metals.

[0117] Clause 8. The lithium battery according to clause 4, characterized in that the composite anode comprises at least one finely distributed interstitial compound selected from the group consisting of: TiN n 、ZrN n , HfN n 、VN n 、NbN n 、TaN n CrN n 、MoN n , WN n 、MnN n ,FeN n , CoN n 、NiN n 、ZnN n Cr 1-n Fe n N, wherein n=0.3 to 1; or Li 7 Mn 4 ;LiMoN 2 ;Li 2.6 Co 0.2 Cu 0.15 Fe 0.05 N; Li 2.7 Fe 0.3 N; Li 3 FeN 2 ;Li2.5 Co 0.2 Cu 0.1 Ni 0.1 N; Li 2.6 Co 0.2 Cu 0.2 N; Li 2.6 Co 0.4 N; TiC, WC; ZrC 1-m , HfC 1-m VC 1-m , NbC 1-m 、TaC 1-m Cr 3 C 2 、MO 2 C.Fe 3 C, wherein m = 0 to 0.5; or ScH 2 , YH o , LaH o , CeH 2 , PrH o , NdH o , SmH o ,EuH o , GdH o , TbH o ,DyH o 、HoH o , ErH o , TmH o , YbH o , LuH o 、TiH 2 , ZrH 2 , HfH 2 , VH, VH 2 , TaH 0.5 , MnH, where o=2 or 3.

[0118] Clause 9. The lithium battery according to clauses 1 to 8, characterized in that the composite anode comprises at least one electrochemically active material selected from the group consisting of: Li 2 NH, MgNH, CaNH, Li 2 Mg(NH) 2 , Li 2 Ca(NH) 2 MgCa(NH) 2 , Li 4 Mg(NH) 3 , Li 2 Mg 2 (NH) 3 、LiNH 2, the electrochemically active material is embedded in a matrix composed of a material containing an electronically conductive or mixed conductive transition metal.

[0119] Clause 10. The lithium battery according to clauses 1 to 9, characterized in that the composite anode comprises a non-metal-based conductivity enhancer, a lithium-providing additive, and a binder.

[0120] Clause 11. The lithium battery according to clauses 1 to 10, characterized in that the composite anode is pressed or calendered.

[0121] Item 12. A lithium battery according to items 1 to 11, characterized in that the cathode comprises at least one anionic redox-active material in the form of a lithium oxygen compound selected from lithium hydroxide, lithium oxide, lithium peroxide and lithium superoxide; and optionally lithium hydride.

[0122] Clause 13. The lithium battery according to clauses 1 to 11, characterized in that the cathode comprises a material selected from LiCoO 2 、LiNiO 2 、Li(Ni,Mn,Co)O 2 、LiNi 0.80 Co 0.15 Al 0.05 O 2 A layered material of the group consisting of: selected from LiMn 2 O 4 and LiNi 0.5 Mn 1.5 O 4 The spinel structure material of the group consisting of: selected from LiFePO 4 and LiMnPO 4 A material having an olivine structure selected from the group consisting of: a non-lithiated metal insertion compound selected from the group consisting of electrolytic manganese dioxide or vanadium oxide, metal fluoride or metal oxyfluoride.

[0123] Item 14. The lithium battery according to Items 1 to 13, characterized in that the weight proportion of the finely distributed transition metal and / or the at least one finely distributed interstitial transition compound in the anode is 1% to 33% by weight.

Claims

1. A rechargeable lithium battery, comprising: a composite anode, wherein the composite anode contains a metal nitrogen compound of the following general formula (I) and / or general formula (II) as an electrochemically active component: Li x M 2 z (NH) 0.5x+z (I) Li m M 2 n (NH2) 1+n (II), where (I) and (II) are present in any mixing ratio, and M 2 is an alkaline earth element selected from the group consisting of Mg, Ca, Sr, Ba and any mixture thereof, wherein x=0-4; z=0-2; m=1 or 0; n=1 or 0, where (m+n)=1, wherein these correspond to the fully discharged most lithium-poor charge states of the metal nitride; A cathode separated from the anode by a separator, wherein the cathode comprises a compound capable of inserting lithium selected from metal oxides, lithium metal oxides, lithium oxides and lithium hydroxide; and comprises an aprotic lithium electrolyte; characterized in that The electrochemically active metal nitrogen compound of the composite anode is embedded in an electronically conductive or mixed conductive network structure containing transition metals, the network structure consisting of transition metals and / or electronically conductive or mixed conductive transition metal compounds, including transition metal nitrides and / or transition metal carbides, The electrochemical potential of the transition metal compound relative to Li / Li+ is <2.5V; And a weight ratio between the component forming the network structure and the metal nitrogen compound is in the range of 1:100 to 1:

5.

2. The lithium battery according to claim 1, characterized in that: The transition metal-containing electronically conductive or mixed conductive network structure comprises a Li / Li + Finely distributed nanoparticle transition metal powders M or interstitial transition metal compounds with an electrochemical potential < 2.5 V.

3. The lithium battery according to claim 1, characterized in that: The composite anode contains elements from Group 3 to Group 12 of the periodic table as transition metal powder.

4. The lithium battery according to claim 1, characterized in that The composite anode comprises an electronically conductive or mixed conductive interstitial transition metal compound selected from a transition metal nitride of at least one element from Group 3 to Group 12 of the Periodic Table of the Elements, a transition metal carbide of at least one element from Group 3 to Group 10 of the Periodic Table of the Elements, and any combination of two or more of the foregoing.

5. The lithium battery according to claim 1, characterized in that: The transition metal powder and / or the mixed conductive interstitial transition metal compound and the electrochemically active metal nitrogen compound are present in a homogeneous mixture in the form of finely distributed amorphous or nanoparticles, wherein the particle size is in the range of 0.1-100 nm.

6. The lithium battery according to claim 1, characterized in that: The weight ratio between the transition metal and / or the electronically conductive or mixed conductive interstitial transition metal compound and the nitrogen-containing active material in the composite anode is in the range of 1:50 to 1:

5.

7. The lithium battery according to claim 3, characterized in that: The composite anode comprises the following as an electronically conductive or mixed conductive network structure containing a transition metal: a finely distributed transition metal powder M, wherein M is selected from Sc, Ti, Zr, Hf, V, Cr, Mo, W, Mn, Fe, Co, Ni, Cu, Ag, Zn, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho, Er, Tm, Yb, Lu and any combination of two or more of the foregoing.

8. The lithium battery according to claim 4, characterized in that: The composite anode comprises at least one finely distributed interstitial compound selected from the group consisting of: (a) TiN n 、ZrN n , HfN n 、VN n 、NbN n 、TaN n CrN n 、MoN n , WN n 、MnN n ,FeN n , CoN n 、NiN n 、ZnN n Cr 1-n Fe n N, wherein n = 0.3 to 1; (b) Li7MnN4, LiMoN2, Li 2.6 Co 0.2 Cu 0.15 Fe 0.05 N; Li 2.7 Fe 0.3 N, Li3FeN2, Li 2.5 Co 0.2 Cu 0.1 Ni 0.1 N; Li 2.6 Co 0.2 Cu 0.2 N.Li 2.6 Co 0.4 N; (c) TiC, WC; ZrC 1-m , HfC 1-m VC 1-m , NbC 1-m 、TaC 1-m , Cr3C2, MO2C, Fe3C, wherein m = 0 to 0.5; and (d) ScH2, YH o , LaH o 、CeH2、PrH o , NdH o , SmH o ,EuH o , GdH o , TbH o ,DyH o 、HoH o , ErH o , TmH o , YbH o , LuH o , TiH2, ZrH2, HfH2, VH, VH2, TaH 0.5 , MnH, where o=2 or 3.

9. The lithium battery according to claim 1, characterized in that: The composite anode comprises at least one electrochemically active material embedded in a matrix consisting of an electronically conductive or mixed conductive material containing a transition metal, wherein the at least one electrochemically active material is selected from Li2NH, MgNH, CaNH, Li2Mg(NH)2, Li2Ca(NH)2, MgCa(NH)2, Li4Mg(NH)3, Li2Mg2(NH)3 and LiNH2.

10. The lithium battery according to claim 1, characterized in that: The composite anode includes a non-metal based conductivity enhancer, a lithium providing additive, and a binder.

11. The lithium battery according to claim 1, characterized in that: The composite anode is pressed or calendared.

12. The lithium battery according to claim 1, characterized in that: The cathode comprises at least one anionic redox-active material in the form of a lithium oxygen compound selected from lithium hydroxide, lithium oxide, lithium peroxide, and lithium superoxide; and lithium hydride.

13. The lithium battery according to claim 1, characterized in that: The cathode comprises a material selected from the group consisting of LiCoO2, LiNiO2, Li(Ni,Mn,Co)O2, LiNi 0.80 Co 0.15 Al 0.05 O2 composed of a layered structure of the material; selected from LiMn2O4 and LiNi 0.5 Mn 1.5 O4 group consisting of spinel structured materials; selected from the group consisting of LiFePO4 and LiMnPO4 olivine structured materials; selected from the group consisting of electrolytic manganese dioxide or vanadium oxides, metal fluorides and metal oxyfluorides consisting of non-lithiated metal insertion compounds.

14. The lithium battery according to claim 1, characterized in that: The weight proportion of the transition metal and / or interstitial transition metal compound in the anode is in the range of 1 wt % to 33 wt %.

15. The lithium battery according to claim 1, characterized in that: The transition metal powder and / or the mixed conducting interstitial transition metal compound and the electrochemically active metal nitrogen compound are present in a homogeneous mixture in the form of finely distributed amorphous or nanoparticles, wherein the particle size is in the range of 1-30 nm.

Citation Information

Patent Citations

  • Nitrogen-containing hydride anodes and electrochemical elements containing nitrogen-containing hydride anodes

    WO2011051290A1

  • Metal imide compounds as anode materials for lithium batteries and galvanic elements with a high storage capacity

    WO2011121084A1

  • Metal imide compounds as anode materials for lithium batteries and galvanic elements with a high storage capacity

    CN103081184A

  • Preparation method for transition metal oxide and complex hydride composite negative electrode material

    CN105895881A

  • Stabilized (partly) lithiated graphite materials, process for preparing them and use for lithium batteries

    CN106537652A